Analisis Komparatif Daya Saing Dosen Dalam Menghadapi Era Masyarakat Ekonomi Asean (Studi Kasus Dosen Fakultas Ekonomi Pada Perguruan Tinggi di Kota Palembang) - Marina Malian (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Facing the era of the ASEAN Economic Community (AEC), lecturers must prepare and increase their competitiveness to be able to compete in high competition. This research aims to analyze the comparative competitiveness of lecturers based on gender, study program and education, case studies at the Faculty of Economics at several private universities in Palembang City. This competitiveness is measured through four indicators, namely English language skills, ability to obtain funding for research, ability to obtain funding for community service and ability to publish articles in journals. By using quantitative methods, this research tries to answer research questions, especially regarding the competitiveness of lecturers and comparative studies between respondents based on gender, study program and education. Based on the analysis carried out, this study concluded that the majority of respondents' competitiveness was low, because out of 100 respondents, 94 respondents had low competitiveness, 4 respondents had medium competitiveness, and none had high competitiveness. In addition, using statistical tools, this research found that there was no difference in the level of competitiveness between male and female lecturers and between lecturers in accounting and management study programs. Researchers recommend that to increase competitiveness, universities must provide ongoing English language training for lecturers and also provide financial support to lecturers to conduct research and community service programs.